Inflammatory Gene Expression Upon TGF-β1-Induced p38 Activation in Primary Dupuytren's Disease Fibroblasts - Bujak, Maro; Ratkaj, Ivana; Markova-Car, Elitza; Jurišić, Davor; Horvatić, Anita; Vučinić, Srđan; Lerga, Jonatan; Baus-Lončar, Mirela; Pavelić, Krešimir; Kraljević Pavelić, Sandra (Frontiers in Molecular Biosciences, 2015)
Objectives: Inflammation is an underlying mechanism behind fibrotic processes and differentiation of cells into myofibroblasts. Presented study therefore provides new data on activation of autoimmune and inflammatory immune response genes that accompany activation of p38 and cell differentiation in primary cells derived from Dupuytren's disease (DD) patients. Methods: Primary non-Dupuytren's disease cells (ND) were isolated from macroscopically unaffected palmar fascia adjacent to diseased tissue obtained from patients diagnosed with the last stage of DD and cultured in vitro. Gene expression, collagen gel contraction assay and analysis of secreted proteins were performed in ND cells treated with TGF-β1 and/or inhibitor of p38 phosphorylation. Results: During differentiation of ND fibroblasts, increased expression of immune response genes PAI-1, TIMP-1, CCL11 and IL-6 was found. These changes were accompanied by increased cell contractility and activation of p38 and its target kinase MK2. Inhibition of p38 phosphorylation reversed these processes in vitro. Conclusions: TGF-β1 induced p38 phosphorylation in ND cells grown from macroscopically unaffected palmar fascia adjacent to diseased tissue from DD patients. This was accompanied by activation of the cytokine genes CCL-11 and IL-6 and secretion of extracellular matrix regulatory proteins PAI-1 and TIMP-1. A combined approach directed towards inflammation and p38 MAPK-mediated processes in DD might be considered for improving management of DD patients and prevention of recurrence.